1996
DOI: 10.1097/00007632-199604010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Degeneration on the Elastic Modulus Distribution in the Lumbar Intervertebral Disc

Abstract: The distribution of elastic moduli is much different between discs with and without degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 27 publications
7
55
0
3
Order By: Relevance
“…15,16 The viscoelastic properties of the goat NP are largely in line with earlier investigations of human, 17,18 pig, 19 and sheep 20 NP, as summarized in Table 1. These findings underscore the potential of the goat as an animal model for disc herniation studies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…15,16 The viscoelastic properties of the goat NP are largely in line with earlier investigations of human, 17,18 pig, 19 and sheep 20 NP, as summarized in Table 1. These findings underscore the potential of the goat as an animal model for disc herniation studies.…”
Section: Discussionsupporting
confidence: 82%
“…Earlier studies have shown that G 00 increases in case of disc degeneration. 18 In this study, we used a plastic compression technique to develop collagen I-based scaffolds with varying concentrations and viscoelastic properties. This is a novel technique that was first described by Brown et al 21 as a form of cell-independent engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the gels were highly elastic, with storage moduli generally 4-5 times larger than loss moduli. To put these data into perspective, typical compressive moduli for native tissue are: nucleus pulposus, 3-310 kPa [33][34][35] ; annulus fibrosus, 29-740 kPa [34][35][36] ; articular cartilage, 0.31-1.237 MPa [37][38][39] ; and meniscus, 0.605-1.03 MPa. 40,41 From these compressive modulus values of native tissues, the 5-6% (w/v) low acyl gellan gum with complex compressive moduli of 324.1 6 6.3 and 407.9 6 10.0 kPa, respectively could be a good candidate for nucleus pulposus and annulus fibrosus replacement, and nearly sufficient for meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this complication, there is consistent evidence that annulus UTS and modulus (normalised stiffness) increase radially outwards, from the inner AF to the disc periphery [3][4][5][6]. This can be attributed to the increasing volume fraction of large and strong collagen Type I fibres in the periphery [7].…”
Section: Introductionmentioning
confidence: 92%